LUG‘ATLARNING SHAKLLANISH TARIXI BORASIDA MULOHAZALAR - Xushboqova Jahona (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
This thesis analyzes the reflections on the history of dictionaries and their formation, which are considered the research source of lexicography. By analyzing the history of dictionaries from a scientific point of view, an opportunity is created to study the changes that have occurred in their development to the present day: similarities and differences.